Konsep Affirmative Action Policy dalam Pengembangan Karir ASN Berbasis Merit - Nurdewi Nurdewi (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
In the context of merit-based development of Human Resources (HR) for the state civil apparatus, the affirmative action policy is used as the basis for implementing the acceleration of equity and improving the quality of human resources for the state civil apparatus. The diversity of ASN achievement requires varied handling in order to create better bureaucratic performance. Law Number 5 of 2014 concerning the State Civil Apparatus (UU ASN) mandates the achievement of a good bureaucracy on a merit basis in accordance with the development of the concept of affirmative action policy. This research method is a qualitative descriptive analysis to produce an in-depth analysis related to the issue of the importance of the affirmative action policy in the development of merit-based Indonesian bureaucratic civil apparatus human resources. The object of this research is in North Maluku Province, precisely in the North Maluku Human Resources Development Agency (BPSDM).